2009
DOI: 10.1007/s11605-009-0807-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Metastasectomy for Testicular Germ Cell Tumors: Is it worth it?

Abstract: Resection of post-chemotherapy hepatic disease is safe, even when combined with resection of extrahepatic residual disease. The varied histologic findings, lack of reliable predictors, and prolonged survival achieved support a multidisciplinary approach which includes surgical resection of hepatic metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Regardless, in patients where surgery is feasible, aggressive management appears justified, as our patients experienced a favorable 3-year estimated cancer-specific survival of 75%, despite liver metastasis usually being associated with a poor prognosis. Since our survival rate is similar to the reported experiences from other centers, our data further supports the potential for favorable survival outcomes after hepatic resection [16][17][18][19].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regardless, in patients where surgery is feasible, aggressive management appears justified, as our patients experienced a favorable 3-year estimated cancer-specific survival of 75%, despite liver metastasis usually being associated with a poor prognosis. Since our survival rate is similar to the reported experiences from other centers, our data further supports the potential for favorable survival outcomes after hepatic resection [16][17][18][19].…”
Section: Discussionsupporting
confidence: 90%
“…However, this 6% rate of histologic discordance is in marked contrast with the 21% seen in our study, as well as other reported experiences. For example, in a study from the Mayo clinic, among 15 patients undergoing hepatic resection for metastatic GCT [17], hepatic histology revealed teratoma or viable GCT in 38% (3/8) of patients with necrosis at extra-hepatic sites [17]. Furthermore, the German Testicular Cancer Study Group also reported a 39% discordance rate between hepatic and extrahepatic sites in 43 patients treated between 1990-1999 [18].…”
Section: Discussionmentioning
confidence: 99%
“…Data on individual histologic subtypes frequently come from small case series [11][12][13][14][15][16][17][18][19]. Therefore, defining benefits of liver resection for individual patients is difficult [6].…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is used as an adjuvant treatment to eliminate residual tumours after chemotherapy or to select patients who will benefit from additional chemotherapy. In the study reported by You et al [50], 11 of the 15 patients were still alive 8 years after hepatectomy.…”
Section: Testicular Cancermentioning
confidence: 92%